فاعلية أداء مديري المدارس الثانوية في مديرية تربية دمشق من وجهة نظر المدرسين فيها - علي, عيسى; علي, جلال (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت هذه الدراسة إلى تعرف درجة فاعلية أداء مديري المدارس الثانوية في مديرية التربية في محافظة دمشق من وجهة نظر المدرسين فيها. ولتحقيق هدف الدراسة تم تطوير استبانة مكونة من ( 44 ) فقرة موزعة على ستة مجالات، كما تم التأكد من صدق الأداة وثباتها، وطبقت الأداة على عينة عشوائية مكونة من(236) مدرساً ومدرسة في المدارس الثانوية الرسمية في مديرية التربية في محافظة دمشق، وقد تم تحليل البيانات المجوعة باستخراج المتوسطات الحسابية، والانحرافات المعيارية، وتحليل التباين، واختبار توكي للمقارنات البعدية، وقد بينت النتائج أن درجة فاعلية أداء مديري مدارس التعليم الثانوي من وجهة نظر المدرسين كانت متوسطة بوجه عام، كما أشارت النتائج إلى أن درجة فاعلية مجال توظيف التكنولوجيا، والمناخ المدرسي، والتخطيط كانت كبيرة، في حين أن درجة فاعلية الأداء في مجالات الاختبارات المدرسية، والتحصيل الدراسي، والقيادة، كانت متوسطة، وأظهرت النتائج عدم وجود فروق ذات دلالة إحصائية تعزى للمتغيرات المستقلة عند مستوى الدالة 0. 05= α على جميع مجالات الدراسة ، عدا متغير الخبرة على مجال الاختبارات المدرسية، وجاءت الفروق لصالح ذوي الخبرة أقل من 5 سنوات، ووجود فروق ذات دلالة إحصائية تعزى لتفاعل الجنس مع المؤهل العلمي في مجال التحصيل الدراسي، وجاءت الفروق لصالح الذكور من حملة الإجازة ، ومجالات : توظيف التكنولوجيا، والمناخ المدرسي، والاختبارات المدرسية، وجاءت الفروق لصالح الإناث من حملة شهادة المعاهد المتوسطة. (The aim of this study was to identify the degree of effectiveness of the performance of the secondary school principals in the Directorate of Education in the province of Damascus from the point of view of teachers. To achieve the goal of the study, a tool consisting of (44) items has been developed and distributed on six areas. The veracity of the tool and its persistence has also been ascertained and applied on a random sample consisting of (236) male and female teachers working in the official schools of the Directorate of Education located in the province of Damascus. The collected data has been analyzed by extracting the arithmetic means, the standard deviations, the analysis of variance, and the post hoc Tukey's test. The results showed that the effectiveness degree of performance of the managers of the secondary schools has recorded an average rate according to the teachers. Whereas, the effectiveness degree of the recruitment technology, school climate, and planning has been high. The effectiveness degree of performance, concerning school tests, academic achievements, leadership, has achieved an average rate. The findings have indicated no statistically significant differences attributable to the independent variables at the function (0.05) on the different fields of the study except of the variable experience degree of school tests. The differences have been in favor of those who have an experience of less than 5 years. A number of statistically significant differences have been detected and which have resulted from the interaction between gender type and the academic qualification within the realm of academic attainment. The differences have been in favor of males holding BA degrees along with those working in different fields such as, recruitment of technology, school climate, and school tests. The differences have been in favor of females holding degrees of intermediate institutes.